The importance of additional intracranial injuries in epidural hematomas: detailed clinical analysis, long-term outcome, and literature review in surgically managed epidural hematomas - Marhold, Franz; Prihoda, Romana; Pruckner, Philip; Eder, Vanessa; Glechner, Anna; Klerings, Irma; Gombos, Jozsef; Popadic, Branko; Antoni, Anna; Sherif, Camillo; Scheichel, Florian (Frontiers in Surgery, 2023)
Epidural hematomas (EDH) occur in up to 8.2% of all traumatic brain injury (TBI) patients with more than half of these patients needing surgical treatment. In many of these patients good recovery with an excellent clinical course in this perilous disease is possible. However, the clinical course is mainly dependent on the presence of additional intracerebral injuries.Few studies exist comparing isolated and combined EDH in detail.We performed a retrospective single center study from April 2002 until December 2014.The mean follow-up was more than 6 years. In addition to the analysis of the diverse clinicoradiological data we performed a systematic literature review dealing with detailed comparison of patients with (combined) and without (isolated) additional intracerebral injuries.We included 72 patients in the study. In increasing age, there is a trend of higher incidence of combined EDH than isolated EDH. Mortality of the cohort was 10%, of which 0% of patients had isolated EDH and 10% of patients had combined EDH. Good recovery was achieved in 69% of patients, of which 91% had isolated EDH and 50% had combined EDH. A subgroup analysis of the different additional intracerebral injuries in combined EDH demonstrated no significant difference in outcome.A systematic literature review identified only 6 studies. Patients with isolated EDH had a statistically significant lower mortality risk (RR: 0.22; 95% CI: 0.12-0.39) and a statistically significant lower risk of unfavorable GOS (RR: 0.21; 95% CI: 0.14-0.31) than patients with combined EDH.An excellent outcome in patients with surgically treated isolated EDH is possible. Furthermore, patients with combined EDH or isolated EDH with low Glasgow Coma Scale (GCS) may have favorable outcome in 50% of the cases. We therefore conclude every possible effort for treatment should be made in this potentially lethal injury.